Characteristics of the Teren Bas Instrument of Orkes Kampoeng Wangak - Viktoria Friski Lestari; Ezra Deardo Purba; Rianti Mardalena Pasaribu (Universitas Negeri Medan, 2025)
Teren Bas is a distinctive musical instrument from Maumere that has developed from the village music traditions of East Flores. In the context of contemporary ethnic music, this instrument has undergone a transformation in both form and function through the musical practices of the group Orkes Kampoeng Wangak based in Yogyakarta. This study explores the characteristics of the Teren Bas instrument as performed by Orkes Kampoeng Wangak, particularly through the song